2012
DOI: 10.1093/protein/gzs094
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a soluble high-affinity receptor domain that neutralizes staphylococcal enterotoxin C in rabbit models of disease

Abstract: Superantigens (SAgs) are a class of immunostimulatory exotoxins that activate large numbers of T cells, leading to overproduction of cytokines and subsequent inflammatory reactions and systemic toxicity. Staphylococcal enterotoxin C (SEC), a SAg secreted by Staphylococcus aureus, has been implicated in various illnesses including non-menstrual toxic shock syndrome (TSS) and necrotizing pneumonia. SEC has been shown to cause TSS illness in rabbits and the toxin contributes to lethality associated with methicill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 44 publications
(82 reference statements)
2
35
0
Order By: Relevance
“…Similarly, blocking SEC function using a high-affinity SEC binding inhibitor resulted in a drastic reduction of vegetation size (32). Although the Newman ⌬sea mutant demonstrated decreased counts within the hearts, we did not observe any obvious aortic valve vegetations from wild-type Newman, although our protocol is not an endocarditis model as valve damage is not actively induced.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similarly, blocking SEC function using a high-affinity SEC binding inhibitor resulted in a drastic reduction of vegetation size (32). Although the Newman ⌬sea mutant demonstrated decreased counts within the hearts, we did not observe any obvious aortic valve vegetations from wild-type Newman, although our protocol is not an endocarditis model as valve damage is not actively induced.…”
Section: Discussionmentioning
confidence: 66%
“…Rabbits are particularly sensitive to the effects of SAgs; using this animal species, deletion of the gene encoding SEl-X from S. aureus USA300 demonstrated reduced mortality from necrotizing pneumonia (29), and deletion of the gene encoding staphylococcal enterotoxin C (sec) from S. aureus MW2 prevented mortality in a rabbit model of sepsis/infective endocarditis (30). Furthermore, engineered highaffinity SAg inhibitors or vaccination with SAg toxoids can protect rabbits from S. aureus pneumonia, infective endocarditis, and sepsis (31)(32)(33). Collectively, these studies show unequivocally that SAgs enhance the severity and lethality of staphylococcal infection.…”
mentioning
confidence: 99%
“…In contrast, the TSST-1-positive strain caused nearly 7 logs more CFU in cardiac vegetations. In a recent study with the use of passive neutralization of SEC in CA-MRSA USA400 strain MW2, administration of V␤-TCRs specific for SEC prevented development of cardiac vegetations (252). Finally, active immunization studies targeting superantigens and cytolysins effectively prevented USA200 S. aureus infective endocarditis (134).…”
Section: Staphylococcal Infective Endocarditis and Superantigensmentioning
confidence: 99%
“…Over the past few years several groups have reported partial protection against S. aureus infections in various models using vaccines or antibodies against SEB, 9 SEA, 10 TSST-1, 11 and SEC. 12 In this issue of Virulence, Aguilar et al 13 report 2 monoclonal antibodies that neutralize SEK, a superantigen produced by most isolates of USA 300, the MRSA clone that is currently circulating and is responsible for most cases of S. aureus invasive disease in the US. 14 SEK was described in 2001 as a potent superantigen that is lethal to rabbits (Orwin I&I 2001) but little is known about the role of SEK in USA300 pathogenesis.…”
mentioning
confidence: 99%
“…22 In another study, treatment with soluble, highaffinity Vb T cell receptor chains specific for SEC reduced the vegetation and bacterial counts in rabbit model of IE. 12 Furthermore, an epidemiological study showed high prevalence of SAgs in isolates from IE cases when compared with isolates recovered from skin infections. 23 The mechanism by which SAgs influence the course of various S. aureus diseases in the absence of TSS remains enigmatic.…”
mentioning
confidence: 99%